Optimizing food waste management in hospitals: a case study of RSUD dr. Loekmono Hadi Kudus for sustainable healthcare services - Falikhatul Ibriza; Maria Ulfa (Poltekkes Kemenkes Bandung, 2026)
Background: Food waste management in hospitals is an important issue in the context of sustainability and operational efficiency. Ineffectively managed food waste can negatively impact both hospital performance and the environment through increased greenhouse gas emissions. Objective: This study aims to analyze the influence of waste management policies, waste sorting practices, staff training, and recycling facilities on sustainable health services at Dr. Loekmono Hadi Kudus Regional Hospital. Methods: A quantitative explanatory research design was employed using a survey approach. Data were collected from 100 purposively selected respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the causal relationships among the latent variables. Results: The findings revealed that waste management policy had a significant positive effect on sustainable food waste management (β = 0.249; p = 0.000). Staff training showed a significant negative effect (β = -0.404; p = 0.000), indicating potential shortcomings in training implementation. Waste separation had no significant effect (β = -0.013; p = 0.866), which may be associated with low staff participation in waste segregation practices. In contrast, recycling facilities demonstrated a very strong positive effect (β = 0.957; p = 0.000). The model achieved an R² value of 0.836, indicating that 83.6% of the variance in sustainable food waste management was explained by the variables included in the model. Conclusion: Sustainable food waste management is strongly influenced by the availability of recycling facilities and supported by effective waste management policies.